The Traditional Game of Throwing Sandals in Learning Narrative Writing for Elementary School Students - Sri Wulan Anggraeni; Rahman; Istikhoroh Nurzaman; Asep Nurhuda; Yayan Alpian (Universitas Pendidikan Ganesha, 2023)
Writing is a very important language skill in school. However, there are still many students who need help with writing. This study analyzes learning to write narratives by applying the traditional game of throwing sandals. The research method used is descriptive qualitative. The research subjects were 18 elementary school students. Data were collected through observation, questionnaires, and story-writing skill tests; After that, the data was evaluated using data reduction, data display, and verification methods. The results showed that learning to write narratives using the traditional game